The last step is to use the Division Property of Equality to solve for x by dividing both sides of the equation by -1, since dividing a number by its negative gives a positive result. This step yields:
x = (-6) / (-1)
Which simplifies to:
x = 6
Jackson solved the problem 3x-8=2(2x-7) using the following steps:
STEP 1: Use Distributive Property to get 3x-8=4x-14
STEP 2: Use Addition Property of Equality to get 3x = 4x-14+8
STEP 3: Combine Like Terms to get 3x = 4x-6
STEP 4: Use Subtraction Property of Equality to get 3x-4x= -6
STEP 5: Combine Like Terms to get (-x)=-6
What is the last step?
double check and explain your answer
1 answer